Endogenous attention to object features modulates the ERP C1 component. Issue 1 (3rd April 2018) - Zani, Alberto; Proverbio, Alice Mado
ABSTRACT: Converging neuroimaging and electrophysiological evidence supports the notion that selective attention can modulate neural activity not only in V1 (BA17)—as early as 40–60 ms post-stimulus—but also at the subcortical level (thalamic lateral geniculate nucleus, LGN). V1 modulation has been documented both in space-based and (especially) object-based selection conditions, most of all in endogenous orienting paradigms. It seems then that an attentional modulation of the ERP C1 response—reflecting V1 modulation—would not be especially favoured by exogenous cuing as far as object-based attention is concerned.